Analisis Manajemen Laba pada Laporan Keuangan Bank Muamalat Bau-Bau di Masa Pandemi Covid-19 Tahun 2021 - Efriani; Ayudiati, Citra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bank Muamalat Indonesia or abbreviated as BMI is the first Islamic bank to comply with Bank Indonesia (BI) regulation. Like a normal bank. BMI conducts its business to earn profits wchich of course is under the guidance and protection of the Indonesia bank whose operations are carried out in sharia and also has principles that must be obeyed to use the interest system. The purpose of this study wasto find out and analyze the indications of earnings managements of Bank Muamalat Indonesia. This study uses total accruals from Healy (Arfani dan Sasongko, 2005). This means that there is earnings management in the financial statements of Bank Muamalat Indonesia for two years